2020
DOI: 10.7554/elife.52589
|View full text |Cite
|
Sign up to set email alerts
|

Application of optogenetic Amyloid-β distinguishes between metabolic and physical damages in neurodegeneration

Abstract: The brains of Alzheimer’s disease patients show a decrease in brain mass and a preponderance of extracellular Amyloid-β plaques. These plaques are formed by aggregation of polypeptides that are derived from the Amyloid Precursor Protein (APP). Amyloid-β plaques are thought to play either a direct or an indirect role in disease progression, however the exact role of aggregation and plaque formation in the aetiology of Alzheimer’s disease (AD) is subject to debate as the biological effects of soluble and aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 68 publications
3
56
0
3
Order By: Relevance
“…A) A scattered plot depicting selected work of optogenetic control of molecular activities in the past three years. Strategies are grouped into three categories: cell signaling (yellow), [ 20,34,38–49,51a,52–59,61,67,69–76,79–83,66 ] organelle manipulation (cyan), [ 84–87,89–100 ] and genetic regulation (magenta). [ 101,102,105–107,109–118 ] Excitation wavelength refers to the light used to activate the optogenetic proteins, which are individually labeled.…”
Section: Spatiotemporal Optical Control Of Intracellular Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A) A scattered plot depicting selected work of optogenetic control of molecular activities in the past three years. Strategies are grouped into three categories: cell signaling (yellow), [ 20,34,38–49,51a,52–59,61,67,69–76,79–83,66 ] organelle manipulation (cyan), [ 84–87,89–100 ] and genetic regulation (magenta). [ 101,102,105–107,109–118 ] Excitation wavelength refers to the light used to activate the optogenetic proteins, which are individually labeled.…”
Section: Spatiotemporal Optical Control Of Intracellular Signal Transductionmentioning
confidence: 99%
“…Although cytotoxicity of Amyloid‐β was confirmed in both soluble and light‐induced solid phases, metabolic damage occurs only in the solid phase upon light stimulation. [ 100 ]…”
Section: Spatiotemporal Optical Control Of Intracellular Signal Transductionmentioning
confidence: 99%
“…Kaur. et al [ 118 ] demonstrated the use of optogenetic Amyloidβ to monitor in vivo protein aggregation while fluorescent optogenetic Amyloid-beta was shown to enable discrimination between metabolic and physical damages in neurodegeneration [ 119 ] as well in vivo settings. Development of cell-free systems, as part of the synthetic biology field, to become a critical platform in biological studies [ 120 ].…”
Section: Wide Biosensing Relevancementioning
confidence: 99%
“…The use of animal models to dissect the underpinnings of human brain disorders is irreplaceable [76], yet studies have to fulfill a tall order of requirements where differences in cellular physiology, species differences, and the differences due to the complexity of the circuitry need to be taken into account while generating meaningful, transferable knowledge. The studies on MOR and NMDAR described above both used cLH rodents [13,64].…”
Section: Perils Of Reliance On Single Models To Understand the Neurobmentioning
confidence: 99%